Effects of Leadership Formation on the Behavior and Academic Performance of Student Leaders in Tomas Claudio Colleges - Delos Santos, Marion (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effects of leadership formation on the behavior and academic performance of student leaders at Tomas Claudio Colleges for the School Year 2025–2026. Using a descriptive survey research design combined with documentary analysis, data were gathered from 284 student leaders and 26 organization advisers across 16 student organizations. A researcher-made questionnaire assessed leadership formation in terms of personal development, decision-making skills, interpersonal skills, and integrity and ethical conduct, while academic performance was measured through the students’ General Weighted Average (GWA) obtained from official records. Findings revealed that most organization advisers were aged 30–39, with 6–10 years of service and holding master’s degrees, while student leaders were mostly 21 years old and above, first-born children, and coming from families with a monthly income of ₱30,000, with parents who were college graduates or undergraduates. The results showed that leadership formation significantly enhances student leaders’ behavior, particularly in terms of integrity and ethical conduct, followed by interpersonal skills and personal development. Decision-making skills were also positively influenced, though to a lesser extent. Significant differences were found between advisers’ and student leaders’ perceptions regarding interpersonal skills and ethical conduct, but not in personal development and decision-making.In terms of academic performance, most student leaders demonstrated very satisfactory to outstanding results, with low variability in grades. A significant relationship was found between leadership formation and academic performance, indicating that stronger leadership development contributes to better academic outcomes.The study concludes that leadership formation plays a vital role in shaping student leaders’ behavior and enhancing academic performance. It recommends strengthening leadership programs, integrating leadership-based learning activities, and implementing standardized mentoring systems to further develop student competencies and support academic success..
Keywords: leadership formation, student leaders, behavior, academic performance, Tomas Claudio Colleges, personal development, decision-making skills, integrity, academic success.